PD-L1 targeting and subclonal immune escape mediated by PD-L1 mutations in metastatic colorectal cancer. Issue 7 (27th July 2021) - Stein, Alexander; Simnica, Donjete; Schultheiß, Christoph; Scholz, Rebekka; Tintelnot, Joseph; Gökkurt, Eray; von Wenserski, Lisa; Willscher, Edith; Paschold, Lisa; Sauer, Markus; Lorenzen, Sylvie; Riera-Knorrenschild, Jorge; et al.
Abstract : Background: In patients with microsatellite stable (MSS) metastatic colorectal cancer (mCRC), immune checkpoint blockade is ineffective, and combinatorial approaches enhancing immunogenicity need exploration. Methods: We treated 43 patients with predominantly microsatellite stable RAS/BRAF wild-type mCRC on a phase II trial combining chemotherapy with the epidermal growth factor receptor antibody cetuximab and the programmed cell death ligand 1 (PD-L1) antibody avelumab. We performed next-generation gene panel sequencing for mutational typing of tumors and liquid biopsy monitoring as well as digital droplet PCR to confirm individual mutations. Translational analyses included tissue immunohistochemistry, multispectral imaging and repertoire sequencing of tumor-infiltrating T cells. Detected PD-L1 mutations were mechanistically validated in CRISPR/Cas9-generated cell models using qRT-PCR, immunoblotting, flow cytometry, complement-dependent cytotoxicity assay, antibody-dependent cytotoxicity by natural killer cell degranulation assay and LDH release assay as well as live cell imaging of T cell mediated tumor cell killing. Results: Circulating tumor DNA showed rapid clearance in the majority of patients mirroring a high rate of early tumor shrinkage. In 3 of 13 patients expressing the high-affinity Fcγ receptor 3a (FcγR3a), tumor subclones with PD-L1 mutations were selected that led to loss of tumor PD-L1 by nonsense-mediated RNA decay in PD-L1 K162fs and protein degradation in PD-L1 L88S. As a consequence, avelumab binding and antibody-dependent cytotoxicity were impaired, while T cell killing of these variant clones was increased. Interestingly, PD-L1 mutant subclones showed slow selection dynamics reversing on avelumab withdrawal and patients with such subclones had above-average treatment benefit. This suggested that the PD-L1 mutations mediated resistance to direct antitumor effects of avelumab, while at the same time loss of PD-L1 reduced biological fitness by enhanced T cell killing limiting subclonal expansion. Conclusion: The addition of avelumab to standard treatment appeared feasible and safe. PD-L1 mutations mediate subclonal immune escape to avelumab in some patients with mCRC expressing high-affinity FcγR3a, which may be a subset experiencing most selective pressure. Future trials evaluating the addition of avelumab to standard treatment in MSS mCRC are warranted especially in this patient subpopulation. Trial registration number: NCT03174405 .